The Implementation of the Sorogan Method in improving the Ability to Read Yellow Books: A Study at Pondok Pesantren Nurul Hidayah Pusat, Sadeng, Leuwisadeng, Bogor - Aulia, Nazla; Kurniawan, Akhmad Kharis; Rizki, Reffy Ananda; Neneng; Maftuhah, Rifa'atul (CV. Lentera Literasi Indonesia, 2025)
This study aims to examine the implementation, effectiveness, and challenges of the sorogan method in teaching classical Islamic texts (kitab kuning) at Pondok Pesantren Nurul Hidayah Al-Khidmah. Employing a descriptive qualitative approach, data were collected through in-depth interviews, observations, and documentation. The findings reveal that the sorogan method is structured into two instructional levels: the basic level for children and the advanced level for adult learners. At the basic level, students rely on teacher guidance, while at the advanced level, learners demonstrate autonomy in reading and translating unvowelled classical texts. The method has proven effective in enhancing students’ reading skills through personalized instruction and direct teacher-student interaction. However, several challenges persist, including limited instructional time, inconsistent teacher commitment, and insufficient Qur’anic literacy among novice students. To address these issues, the pesantren has introduced Qur’anic literacy programs and strengthened dormitory-based instructional supervision. The key contribution of this study lies in reaffirming the pedagogical relevance of the traditional sorogan method within the framework of modern, learner-centered education. The results are expected to inform educators, pesantren administrators, and policymakers in designing more adaptive, effective, and sustainable strategies for teaching classical Islamic texts in contemporary educational settings.